Perjanjian Dengan Maut dan Galau Di Laut Selatan: Representasi Jejak Mistis Nyai Roro Kidul dalam Sistem Kepercayaan Masyarakat Jawa - Tisnawijaya, Christy (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
The mystical figure of Nyi Roro Kidul has been passed down from generation to generation and manifested in worship rituals, sacred places, dances, paintings and films. Even though the story of Nyi Roro Kidul contradicts modern religion, it is still an aspect of the Javanese belief system. This article discusses the role of the Nyi Roro Kidul myth as part of the Javanese belief system, which is represented in two Indonesian novels, Perjanjian dengan Maut by Harijadi S. Hartowardojo (1976) and Galau di Laut Selatan by Martha Hadimulyanto (1993). The data, narrations and characters' dialogues were obtained through reading and note-taking techniques and discussed using the library study method, namely descriptive analysis of intrinsic elements. The discussion results show that the myth of Nyi Roro Kidul influences the characters' religiosity and thus affects their decision-making when facing conflicts.